Regular, sustained-release morphine for chronic breathlessness: a multicentre, double-blind, randomised, placebo-controlled trial. Issue 1 (26th September 2019) - Currow, David; Louw, Sandra; McCloud, Philip; Fazekas, Belinda; Plummer, John; McDonald, Christine F; Agar, Meera; Clark, Katherine; McCaffery, Nikki; Ekström, Magnus Pär
Abstract : Introduction: Morphine may decrease the intensity of chronic breathlessness but data from a large randomised controlled trial (RCT) are lacking. This first, large, parallel-group trial aimed to test the efficacy and safety of regular, low-dose, sustained-release (SR) morphine compared with placebo for chronic breathlessness. Methods: Multisite (14 inpatient and outpatient cardiorespiratory and palliative care services in Australia), parallel-arm, double-blind RCT. Adults with chronic breathlessness (modified Medical Research Council≥2) were randomised to 20 mg daily oral SR morphine and laxative (intervention) or placebo and placebo laxative (control) for 7 days. Both groups could take ≤6 doses of 2.5 mg, ' as needed ', immediate-release morphine (≤15 mg/24 hours) as required by the ethics review board. The primary endpoint was change from baseline in intensity of breathlessness now (0–100 mm visual analogue scale; two times per day diary) between groups. Secondary endpoints included: worst, best and average breathlessness ; unpleasantness of breathlessness now, fatigue; quality of life; function; and harms. Results: Analysed by intention-to-treat, 284 participants were randomised to morphine (n=145) or placebo (n=139). There was no difference between arms for the primary endpoint (mean difference −0.15 mm (95% CI −4.59 to 4.29; p=0.95)), nor secondary endpoints. The placebo group used more doses of oral morphine solution during the treatment period (mean 8.7 vs 5.8 doses; p=0.001). The morphine group had more constipation and nausea/vomiting. There were no cases of respiratory depression nor obtundation. Conclusion: No differences were observed between arms for breathlessness, but the intervention arm used less rescue immediate-release morphine. Trial registration number: ACTRN12609000806268.